Interpretation of Phraseological Units Using Chinese Language in Russian-Chinese Phraseological Dictionaries - Di Liu; Fanhong Meng (Научный диалог, 2023)
The description of Russian phraseological units by means of the Chinese language in lexicographic practice is considered. Dictionary articles, their structure and content from six main phraseological dictionaries published in China from the second half of the last century to the present day are analyzed. The results of the research showed that the explanation of Russian phraseology in these lexicographic sources is carried out in two ways: through interpretation and selection of a similar expression. It is shown that the second method is implemented in two variants: as interpretation-translation and literal translation. It has been established that interpretation-translation differs from actual interpretation and literal translation by the presence of two equivalent functions: explanation and interpretation. The compound description model «analogous expression + additional interpretation», which is most often used in dictionary articles where there is no proper interpretation and etymological information is also revealed. On the contrary, when they are present in the dictionary article, a Chinese analogous expression is usually used as a variant of the explanation of the Russian phraseological unit. The authors come to the conclusion that the volume of dictionary articles and models of description of Russian phraseology depend on the goals of dictionary compilers: a brief reference presentation of phraseology, a detailed explanation through an extensive etymological commentary, representation of materials for learning by demonstrating examples, etc.